PENERAPAN HIGH KEY LIGHTING DALAM MENDUKUNG MOOD RINGAN ANIMASI 3D KOMEDI - Stefanus Feby Nauvalim; Mahendradewa Suminto; Troy (Pusat Penerbitan LPPM ISI Bali, 2026)
High Key Lighting in cinematography is characterized by high light intensity and low shadow contrast, and it is frequently applied in both live-action and 3D animated films for the purposes of establishing mood or achieving aesthetic goals. Although this technique is often associated with a light and cheerful impression, there is a lack of in-depth studies formulating specific technical parameters for its application within the animated comedy genre. Therefore, this research aims to analyze, formulate, and test the visual impression generated by the High Key Lighting technique in the lighting design of animated comedy films. This exploration focuses on identifying the most effective combination of key light, fill light, and contrast ratio to emphasize a lighthearted and humorous impression. The results of this research are expected to provide technical guidelines for lighting designers in the production of animated comedy films.